Generidade e politicidade no último Lukács - Rezende, Claudinei Cássio de [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
This search analyzes the concepts of genericity and politicity in the last philosophical trajectory of György Lukács (1956-1971). The analyzed texts are Ontology of Social Being, including its Introduction, and their latest political writings, specially Democratisation Today and Tomorow. The crucial question of the ontology of social being for Lukács it is shrouded the elucidation of human genericity, peculiar moment the sphere of biological being that, when cleaved with nature, stands at a completely unprecedented genericity, due to the appearance of putting teleological, in other words, the acts aimed at finalistic transformation of the world. Fixing the teleological put how generator organism of genericity of social being, and to secure the dissemination of teleological positions how the dynamic content of social life, Lukács prevents confusion between the life of nature and society life: the firts, the first is dominated by the spontaneous causality, non-teleological; while the second consists of the acts of praxis of single individuals. In this way, Lukács is faced with the perception of alternative character of all human resolution, verifying that the set of teleological putting generates a pose causality wich is controlled only partially for single individual. With the development of a qualitatively wider genericity, humans now have greater control over their alternatives, and over the results of their finalistics actions. The politics is one of the moments of the secondary teleological put, so, because such finalistic act aims to influence the actions of other single individuals, so that politics is a kind of practice focused on social totality. The action field of single individuals is increasing every social complexity, which causes a deployment process of genericity, through political acts originating from alternative chain. Politicity and genericity appear in the mature stage of Lukacs with inextricable bonds; because the...

Esta tese analisa as concepções de generidade e politicidade na última trajetória filosófica de György Lukács (1956-1971). Os textos analisados são Para uma ontologia do ser social, incluindo seus Prolegômenos, e os seus escritos políticos derradeiros, com notado destaque a O processo de democratização. A questão crucial da ontologia do ser social em Lukács está envolta à dilucidação da generidade humana, momento peculiar da esfera do ser biológico que, ao cindirse com a natureza, eleva-se a uma generidade completamente inédita devido ao surgimento do pôr teleológico, isto é, os atos que visam a transformação finalística do mundo. Ao fixar o pôr teleológico como organismo gerador da generidade do ser social, e ao fixar a disseminação das posições teleológicas como o conteúdo dinâmico da vida social, Lukács impossibilita a confusão entre a vida da natureza e a vida da sociedade: a primeira é dominada pela causalidade espontânea, não-teleológica; enquanto a segunda é constituída pelos atos da práxis dos indivíduos singulares. Neste sentido, Lukács se depara com a percepção do caráter alternativo de toda resolução humana, verificando que o conjunto dos pores teleológicos gera uma causalidade posta que apenas em partes é controlada pelo indivíduo singular. Com o desenvolvimento de uma generidade qualitativamente mais ampla, os homens passam a ter maior controle sobre suas alternativas e sobre os resultados de seus atos finalísticos. A política, então, é um dos momentos do pôr teleológico secundário, pois tal ato finalístico visa a influenciar os atos dos outros indivíduos singulares - de modo que a política é um tipo de práxis voltada para a totalidade social. O campo de ação dos indivíduos singulares é aumentado a cada complexificação social que origina um processo de desenvolvimento da generidade através dos atos políticos oriundos da cadeia de alternativas. Politicidade e...
Keywords: Lukács, György 1885-1971; Ontologia; Existencialismo; Filosofia marxista; Communism